An extended layerwise spectral finite element framework for delamination growth simulation in laminated composite strips. (15th November 2021) - Siorikis, D.K.; Rekatsinas, C.S.; Chrysochoidis, N.A.; Saravanos, D.A.
Abstract: A computational framework is presented for the delamination propagation analysis in laminated composite strips that combines an extended high-order layerwise model and a spectral finite element with high-order spatial approximation in the plane of the structure. The extended layerwise laminate mechanics approximate the through-thickness fields using Hermite cubic splines, while the discontinuities in displacement induced by a delamination crack are treated as generalized damage degrees of freedom (DOFs). The layerwise mechanics are integrated into a novel spectral strip finite element, which involves integration points collocated with the nodes, thus providing accurate nodal predictions of the interlaminar stresses on the interface and ahead of the delamination crack tip. Strain energy release rate is predicted by adapting the VCCT method to rely exclusively on the damage DOFs. Finally, an iterative solution method is developed that takes advantage of the damaged DOFs to quickly predict the crack propagation without remeshing. The proposed numerical scheme is applied to mode I, II and mixed-mode delamination fracture problems and is validated vs. reference literature solutions, experimental results and standard 2D plane-strain FE models. The numerical results ultimately illustrate the capacity of the present method to provide accurate predictions with moderately coarse meshes and high computational speed.